2022
DOI: 10.1186/s12885-022-09771-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and interplay of esophageal microbiota in esophageal squamous cell carcinoma

Abstract: Background Esophageal microbiota may influence esophageal squamous cell carcinoma (ESCC) pathobiology. Therefore, we investigated the characteristics and interplay of the esophageal microbiota in ESCC. Methods We performed 16S ribosomal RNA sequencing on paired esophageal tumor and tumor-adjacent samples obtained from 120 primarily ESCC patients. Analyses were performed using quantitative insights into microbial 2 (QIIME2) and phylogenetic investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…35,36 Similar situations are also observed for Gemella and Streptococcus. Notably, we identified an enrichment of Fusobacterium and depletion of Streptococcus in ESCC lavage samples, which is consistent with some previous studies based on tissue specimens 37,38 but different from those inferred from oral rinse or saliva samples, which showed a reduction of Fusobacterium or an enrichment of Streptococcus in the cancer group. 39,40 This discrepancy suggests that local fluids from disease lesions and tumor tissues, rather than distant specimens, are more representative in characterizing host-microbiota interactions.…”
Section: Discussionsupporting
confidence: 90%
“…35,36 Similar situations are also observed for Gemella and Streptococcus. Notably, we identified an enrichment of Fusobacterium and depletion of Streptococcus in ESCC lavage samples, which is consistent with some previous studies based on tissue specimens 37,38 but different from those inferred from oral rinse or saliva samples, which showed a reduction of Fusobacterium or an enrichment of Streptococcus in the cancer group. 39,40 This discrepancy suggests that local fluids from disease lesions and tumor tissues, rather than distant specimens, are more representative in characterizing host-microbiota interactions.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, denser and more complex association networks were formed in tumor-adjacent tissues than in tumor-adjacent tissues. In addition, alterations in microbial symbiotic networks and functional pathways in ESCC tissues may be involved in the oncogenic process of the local microenvironment of ESCC ( 16 ).…”
Section: Microbial Diversity In Tmementioning
confidence: 99%
“…Several case–control studies (Table 1) have revealed a different population of esophageal microbiota in ESCC patients compared to healthy individuals by quantitative polymerase chain reaction (qPCR) 39 or 16S rRNA sequencing 40–46 . Reduced diversity of esophageal microbiota has previously been observed in a patient with ESCC 43 .…”
Section: Dysbiosis In Esophageal Squamous Cell Carcinomamentioning
confidence: 99%